Thermal noise in linear damped systems - Mallinson, J.C. (IEEE transactions on magnetics, 2002)
It is frequently assumed that estimating the noise, or thermal fluctuations, in a damped linear system necessarily depends on knowing the precise magnitude of the damping or energy dissipative component of the system. This paper proves that this notion is incorrect by considering the noise power of a resistor. It then shows that the magnetization fluctuation noise power of a spin-valve giant magnetoresistive head, a subject of considerable current interest, can be analyzed in a particularly simple and straightforward manner without knowing the exact value of the gyromagnetic damping factor.